Studies on alpha-synuclein and islet amyloid polypeptide interaction - Wang, Ye; Bergström, Joakim; Ingelsson, Martin; Westermark, Gunilla T. (Frontiers in Molecular Biosciences, 2023)
Parkinson's disease and type 2 diabetes have both elements of local amyloid depositions in their pathogenesis. In Parkinson's disease, alpha-synuclein (aSyn) forms insoluble Lewy bodies and Lewy neurites in brain neurons, and in type 2 diabetes, islet amyloid polypeptide (IAPP) comprises the amyloid in the islets of Langerhans. In this study, we assessed the interaction between aSyn and IAPP in human pancreatic tissues, both ex vivo and in vitro. In the pancreatic tissues, aSyn co-localizes with IAPP intracellularly, while aSyn is absent in the extracellular amyloid deposits. We demonstrate the presence of aSyn in secretory granules of β-cells and some α-cells in human islets. Bimolecular fluorescence complementation (BiFC) assay, where the development of a fluorescent signal is indicative of protein contact, was used to study αSyn and IAPP interaction. Co-expression of aSyn/aSyn, and IAPP/IAPP in HEK293 cells resulted in 30 % and 20 % fluorescent cells, respectively, while aSyn/IAPP co-expression resulted in 10% fluorescent cells. Preformed aSyn fibrils seeded IAPP fibril formation in vitro, but adding preformed IAPP seeds to aSyn did not change aSyn fibrillation. In addition, mixing monomeric aSyn with monomeric IAPP did not affect IAPP fibril formation. Knockdown of endogenous aSyn did not affect β cell function or viability, nor did overexpression of aSyn affect β cell viability. Therefore, despite the proximity of aSyn and IAPP in β-cells and the detected capacity of preformed aSyn fibrils to seed IAPP in vitro, it is still an open question if an interaction between the two molecules is of pathogenic significance for type 2 diabetes.